Stabilization of collapsible soils with nanomaterials, fibers, polymers, industrial waste, and microbes: Current trends - Khodabandeh, Mohammad Ali; Nagy, Gábor; Török, Ákos (Construction & building materials, 2023)
•The review covers nanomaterials, fibers, polymers, microbes, and industrial waste materials.•The physicochemical properties of additives used in soil stabilization are discussed.•The interaction mechanisms between collapsible soils and additives are reviewed.•The mechanical properties of stabilized collapsible soils are highlighted.•The challenges and research gaps of collapsible soil stabilization are identified. Collapsible soils are susceptible to high and relatively sudden volume change after wetting under a specific load. They tend to have a high initial void index (more than 40%), a low saturation degree (less than 60%), a high silt content (greater than 30%), and quick softening after reaching humidity (loss of bonding). Due to the settlement of the underlying soil after wetting, collapsible soils under the foundation of industrial or residential buildings can cause irreversible and significant damage to the supporting structures. In recent years, more attention has been paid to enhancing the physical and mechanical properties of collapsible soils. This research has comprehensively investigated the feasibility and efficiency of treating collapsible soils with a great variety of stabilization materials including nanomaterials, fibers, polymers, industrial waste materials, and biological techniques. Collapse potential, shear strength parameters, unconfined compressive strength (UCS), permeability reduction, swelling, and durability improvement of treated collapsible soils were investigated. This paper discusses the mechanism of how each material enhances the strength of the soil. According to previous research, using a small amount of nanomaterials, fibers, and polymers (less than 4% of dry mass soil) resulted in a significant change and improvement in soil parameters. However, for industrial waste materials, such as textile slug and marble dust, more proportions (about 30%) would be beneficial.